2006
DOI: 10.2353/ajpath.2006.051042
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Chemokine Expression by NaCl Occurs Independently of Cystic Fibrosis Transmembrane Conductance Regulator in Macrophages

Abstract: Chronic pulmonary inflammation and infection are the leading causes of morbidity and mortality in cystic fibrosis (CF). While the effect of mutation of the cystic fibrosis transmembrane conductance regulator (CFTR) on airways remains controversial, some groups have demonstrated increases in Na(+) and Cl(-) in CF airway surface liquid compared to normal airways. We investigated the consequences of NaCl on pro-inflammatory chemokine and cytokine production by macrophages. Stimulation of mouse macrophages with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…This impairment in ROS release by Cftr-deficient macrophages also decreases the bactericidal capability of these cells against P. aeruginosa. In contrast, Cftr deficiency did not affect the cytokine release response by these lung macrophages, a finding that is consistent with those of previous studies showing that Cftr is not involved in the production of cytokines (KC and MIP2) by LPSstimulated macrophages (30). This situation is in marked contrast to that in Cftr-deficient epithelial cells, which show a marked increase in the constitutive release of proinflammatory cytokines, such as IL-1 and IL-8 (5, 31, 32). )…”
Section: Discussionsupporting
confidence: 82%
“…This impairment in ROS release by Cftr-deficient macrophages also decreases the bactericidal capability of these cells against P. aeruginosa. In contrast, Cftr deficiency did not affect the cytokine release response by these lung macrophages, a finding that is consistent with those of previous studies showing that Cftr is not involved in the production of cytokines (KC and MIP2) by LPSstimulated macrophages (30). This situation is in marked contrast to that in Cftr-deficient epithelial cells, which show a marked increase in the constitutive release of proinflammatory cytokines, such as IL-1 and IL-8 (5, 31, 32). )…”
Section: Discussionsupporting
confidence: 82%
“…Since other chemokines or chemotactically active factors might play important roles in this system, we assessed the role of the transcription factor tonicity-responsive enhancer binding protein (TonEBP), which protects cells from osmotic stress [10], [11], [12], [13] and which previously had been shown to control the transcription of chemokine genes, too [9], [14]. We thus investigated a possible role of TonEBP in salt-dependent chemotaxis using RAW264.7 macrophages with a stable TonEBP overexpression as described previously [2].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that increases in the NaCl concentration to osmolalities of approximately 500–630 mOsm/kg were sufficient to promote the release of tumor necrosis factor (TNF) [34, 35] and chemokine (C-X-C motif) ligand 2 (CXCL2; macrophage inflammatory protein-2) [34] from macrophages in the absence of any additional inflammatory priming. Ip and Medzhitov reported that an increase in the NaCl concentration by 100 mM to a total osmolality of approximately 500 mOsm/kg in lipopolysaccharide (LPS)-treated cells promoted caspase-1-dependent IL-1β- and IL-1α-release from macrophages [36], while an increase of 40 mM NaCl compared to standard cell culture conditions alone were not sufficient to promote the release of IL-1 in LPS-treated cells [37].…”
Section: Salt Gradients In the Kidney And Their Impact On Mononuclearmentioning
confidence: 99%